75/11=-x-2x+6

Simple and best practice solution for 75/11=-x-2x+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 75/11=-x-2x+6 equation:


x in (-oo:+oo)

75/11 = 6-x-(2*x) // - 6-x-(2*x)

x+2*x+75/11-6 = 0

3*x+9/11 = 0 // - 9/11

3*x = -9/11 // : 3

x = -9/11/3

x = -3/11

x = -3/11

See similar equations:

| 5+4x+1/2x=41 | | x-1/2+x=11/2 | | 1+2x+2/5x=59/35 | | x+5+5/7x=31/5 | | 7x-5+5x=-125 | | -4/5x-4/9-4x=-1964/45 | | 4x+1/3+5x=109/3 | | 2/9+6x+4x=2/9 | | 1/2x+1/4+5/6x=47/60 | | 5/7x+3+3/5x=-33/35 | | 1/2=-1/3x+5/6x+2 | | -9+2/3x+1/2x=-142/15 | | 44=7x-x+2 | | 49=4x+2x+1 | | 212/7=3x-6x+2/7 | | 53/9=5x-7x+5 | | 5/7-2x+6x=257/7 | | 1/3x+1-1/7x=205/189 | | -3/8-x-3/5x=-221/120 | | 14=7x+x+6 | | 2/3x+4/7+6/7x=260/231 | | 2+2/3x+x=22 | | 7x+5+7x=117 | | -1/3-2x+4/7x=-67/21 | | -3/8=4/5x-x-3/8 | | 5-2x+1/2x=61/14 | | 2/3-2/5x+x=16/15 | | 1-4x+2/3x=21/11 | | 6=-x+x+6 | | -7x-5+1/3x=-85/9 | | x+3+5x=39/7 | | 7+3x(-5)= |

Equations solver categories